Psychological well‐being and family distress of Italian caregivers during the COVID‐19 outbreak. Issue 5 (12th December 2021) - Fusar‐Poli, Laura; Surace, Teresa; Meo, Valeria; Patania, Federica; Avanzato, Chiara; Pulvirenti, Alfredo; Aguglia, Eugenio; Signorelli, Maria Salvina
Abstract: The present study aimed to investigate the personal well‐being and family distress of Italian caregivers during the lockdown. Five hundred sixty‐five family caregivers and 638 age‐ and sex‐matched noncaregivers completed a web‐based survey. The following scales were administered to all participants: General Health Questionnaire‐12 items (GHQ‐12), Insomnia Severity Index (ISI), Brief Resilient Coping Scale (BRCS), and Family Distress Index (FDI). Caregivers were also asked to provide information about their family members with disabilities. Individual and family distress, as well as insomnia, were significantly higher in caregivers than controls. Contrariwise, caregivers reported lower resilience levels. Multiple linear regression showed that distress was higher in caregivers living in Central and Southern Italy. Individual well‐being was negatively predicted by low independence measured by the activities of daily living (ADL). Family distress was higher in households of psychiatric patients. Finally, low resilience levels appeared as the strongest predictors of both individual and family distress. The lockdown caused severe distress among caregivers and families of people with disabilities. Support networks for people with disabilities and their families are fundamental to prevent severe consequences from a psychological, social, and economical point of view.